PERGESERAN BAHASA BALI SEBAGAI BAHASA IBU DI ERA GLOBAL (KAJIAN PEMERTAHANAN BAHASA) - I KADEK MUSTIKA (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
The people of Bali experience a very rapid development in line with the development of the current globalization. These developments cover various aspects of life, one of them is the sociocultural aspect, especially the language. Linguistically, the development of people who only know and use the Balinese language becomes bilingual and even multilingual (local, national and foreign languages). This affects the loyalty and attitude of the language of the community and causes the existence of the use of Balinese language as the mother tongue has decreased, both in quality and quantity. This phenomenon occurs in many urban and tourism areas. Important efforts that must be done is to evoke loyalty and positive language attitude towards Balinese speakers, especially in the family environment. In addition, the role of government is also needed in the preservation of the Balinese language. In preserving the Balinese language as a mother tongue can not be separated from various challenges and constraints, both internal and external.